Host instars preference, density-dependent parasitism and behavioral perspective of parasitoids (Aphidius colemani, Aphidius matricariae and Aphelinus abdominalis) in Aphis glycines and Aphis gossypii - Rasool,Bilal (2022)
ABSTRACT Three parasitoid species Aphidius colemani, Aphidius matricariae (Hymenoptera: Braconidae) and Aphelinus abdominalis (Hymenoptera: Aphelinidae) were evaluated concerning their parasitism potential in two aphid species, Aphis glycines and Aphis gossypii (Hemiptera: Aphididae). The feeding of these two aphid species, even at low sums, can significantly damage photosynthesis and is found to transmit many kinds of plant viruses, which impact potential adverse effects on the plants. The overall parasitization on all nymphal ages in As. glycines was accomplished by Ad. colemani (60.50%), Ad. matricariae (49.16%) and Al. abdominalis (40%), while in As. gossypii parasitism exhibited by Ad. colemani (79.48%), Ad. matricariae (65.33%) and Al. abdominalis (58.83%). Aphelinus abdominalis exhibited the lowest parasitism in both given species as hosts. Significant differences in parasitism of different parasitoids and host species were observed. Concerning the preference of nymphal instars, we found that parasitoids species prefer to parasitize 1st- 4th instars in As. gossypii while in As. glycines 2nd, 1st, 3rd and 4th. Our results showed that the parasitism increases with the increase of parasitoid numbers and hosts densities.